Kepemimpinan Transformatif dan Budaya Kerja - Hasanah, Nafi'atul; Maunah, Binti (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2023)
Transformational leadership and work culture are two important elements in organizations that are interrelated and have a significant influence on organizational performance and success. The purpose of this research is to determine studies on transformative leadership and work culture. This research is a type of literature review research. The literature review shows that there is a positive relationship between transformational leadership and work culture. Transformational leaders can foster a positive work culture by encouraging innovation, collaboration and continuous learning. A positive work culture, in turn, can increase employee motivation and performance. This research provides information and explains that a transformative leadership and work culture that is able to understand and respect subordinates based on subordinates' needs and pay attention to the desire for achievement will have an impact on educational institutions, both schools and madrasa.